Menumbuhkan Nilai-Nilai Karakter melalui Pendidikan Khat Al-Arabiy: Studi Kasus di Sekolah Kaligrafi Al-Quran (Sakal) Pondok Pesantren Mambaul Ma'arif Denanyar Jombang - Roisudin, Ayi Sisma (Didaktika Religia, 2015)
The purpose of this study was to examine the understanding character education, education of khat}t} al-‘Arabiy, and the character education that grows khat}t} al-‘Arabiy. The research used qualitative approach. The researcher came the research field as a data collector in Qur'an Calligraphy School (SAKAL) Boarding School Mamba'ul Ma'Arif Denanyar Jombang. The data collection methods used were interviews, observation, and documentation. The analysis of the data is data reduction, data description, and drawing conclusions.The results of the study reveal that the history of khat}t} al-‘Arabiyappearedin Bani Umayyah and continued to develop to the period of Bani Abbasiyah. Then there appeared a calligrapher, Mrs. Muqlah, who later found the writing styles adopted from khat}tquficalled aqlam al-syittah such as: nash}i, thuluth, diwani>, farisi, riq’ah, and qufi.Character education that growsfrom khat al-'Arabiy education are among others religious, honest, discipline, hard working, creative, independent, appreciative, communicative, responsible. The process of establishing character at SAKAL is called taqlidi, which uses sanad as in the memorization of the Koran.